2008
DOI: 10.1182/blood.v112.11.4878.4878
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic Profile of Acute Leukemia: Critical Analysis and Insights Gained at a Tertiary Care Center in India

Abstract: The purpose of this retrospective study, the largest series in our country, was to illustrate the spectrum of subtypes and the immunophenotypic features of cases referred as acute leukemia (AL). Morphological diagnosis was correlated with cytochemical stains, immunophenotyping, and molecular genetic studies including fluorescent in-situ hybridization (FISH) and polymerase chain reaction (PCR). Two thousand five hundred and eleven consecutive new referral cases of Acute Leukemia (AL) between January 1, 2003 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
2
5
1
Order By: Relevance
“…However, other national and international studies have reported that M4 -M5 subtypes are the most common [4] [10]. For ALL, B-ALL was more frequent than T-ALL (85.7%) & (14.3%) respectively which agreed with other studies [11] [12].…”
Section: Discussionsupporting
confidence: 89%
“…However, other national and international studies have reported that M4 -M5 subtypes are the most common [4] [10]. For ALL, B-ALL was more frequent than T-ALL (85.7%) & (14.3%) respectively which agreed with other studies [11] [12].…”
Section: Discussionsupporting
confidence: 89%
“…Our study reported incidence (80.4%) of B-ALL which was similar to other Pakistani studies (78.5-87%) 10,15 as well as an Indian study by Madhumathi et al 16 However studies from West 10,14,17 reported between 72.9 and 91% frequency. Among lymphoblastic leukaemia, 13-23% of T-ALL cases were reported in other studies from Pakistan in last 10 years 10,11,15,18,19 while similar distribution was reported from India 12,13 with concordant distribution reported in the present study. Studies from West reported a relatively lower frequency.…”
Section: Discussionsupporting
confidence: 90%
“…1,10 A study conducted by Amna et al from Pakistan reported 83.3% ALL, 11 two studies from India reported 76.9 and 77.84% 12,13 while the present study has reported 77.2% cases of ALL. Similar Pakistani study reported 14.7% AML cases 11 however the incidence of AML was slightly higher in Indian studies 12,13 and was similar to present study. In terms of MPAL Indian studies reported 1.1-2.3% while our study had slightly low incidence i.e.…”
Section: Discussioncontrasting
confidence: 39%
“…32 33 34 35 36 B-ALL constituted 76% of all ALL that comprised of predominantly CALLA positive ALL in 73%, early precursor pro B-ALL in 3%. 33 The World Health Organization classification of hematopoietic and lymphoid tissue (2017) defines B lymphoblastic leukemia/lymphoma into various subtypes including “B lymphoblastic leukemia/lymphoma with 7 recurrent genetic abnormalities.” 1 Conventional cytogenetics, interphase FISH, RT-PCR find application in the detection of recurrent genetic abnormalities as they play a pivotal role in prognostication, selection of therapy, and response to treatment. 1 13 31 32 33 34 35 36 37…”
Section: Discussionmentioning
confidence: 99%